Time as a Founding Factor in Architectural Thought - Heba Abbas Hameed; Arshad Alanizi (Journal of Techniques)
The research dealt with the concepts of time and architectural thought and the extent of the influence of Ideas derived from the element of time on the variation and differentiation of architectural movements and schools, by reviewing a group of vocabulary such as nostalgia, present, and looking forward to the future, the null of the present and immortality in architecture and the null or deferred future, and the study of the duration of its reflection on architectural thought to lead to the differentiation of each of the architecture of Mesopotamia, Classical architecture, Modern architecture, Post-modernism, and Autonomous architecture, Deconstruction architecture according to these terms. The problem of the research was the lack of clarity on the influence of the element of time and its role in the differentiation of architectural thought. The main goal of the research is to focus on the role of the element of time in the differentiation and uniqueness of architectural thought. As for the research hypothesis, it focused on emphasizing the role of thought that distinguishes time in the differentiation of architectural thought, which in turn guarantees the uniqueness of societies, and the most important finding of the research is that Classical architecture is distinguished by its interest in the principle of nostalgia, and that there are some trends in Contemporary Iraqi Architecture based on the principle of nostalgia represented by nostalgia for formal elements, and that modern architecture urged in most of its buildings nostalgia for the present.